Peran Manajemen Risiko dalam Pengembangan Layanan Pergudangan Modern: Studi pada Secure Stash - Caecilia Austin Flacia Tjandra; Rhian Indradewa; Edi Hamdi; Muhammad Dhafi Iskandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
In order to preserve sustainability and accomplish organizational strategic goals, risk management is crucial, particularly for businesses involved in logistics and warehousing. This study uses the ISO 31000:2018 framework to examine how risk management is applied in Secure Stash. Implementing risk management helps the organization achieve its short-, medium-, and long-term objectives, including boosting partner and customer trust, operational effectiveness, and business sustainability, while also safeguarding it from internal and external threats. The ISO 31000:2018 risk management framework, which comprises risk management principles, structures, and processes, was applied in this study using a qualitative descriptive methodology. The study's findings demonstrate that applying integrated, organized, and sustainable risk management concepts can boost risk management efficacy and aid in the strategic decision-making of the business. Improved organizational performance and operational stability are other benefits of incorporating risk management into all corporate operations. The study's conclusion demonstrates how applying risk management based on ISO 31000:2018 on Secure Stash offers a methodical and flexible framework for handling the changing dynamics of the business environment. In order to keep their risk management system up to date with changes in strategy, technology, and external circumstances, businesses are recommended to keep evaluating and improving it.